2021
DOI: 10.3390/ijms22063209
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Tau Protein Level and Phosphorylation State in the Brain of the Autistic-Like Rats Induced by Prenatal Exposure to Valproic Acid

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by deficient social interaction and communication besides repetitive, stereotyped behaviours. A characteristic feature of ASD is altered dendritic spine density and morphology associated with synaptic plasticity disturbances. Since microtubules (MTs) regulate dendritic spine morphology and play an important role in spine development and plasticity the aim of the present study was to investigate the alterations in the content of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 119 publications
2
18
1
Order By: Relevance
“…Our results have shown significant abnormalities of P-ERK and CDK5 in the brains of BTBR mice, which could be rescued by SKI-II intervention. In contrast to our study, other studies have demonstrated that ERK1/2 and CDK5 are both activated in the hippocampus of VPA rats [ 51 ], possibly because different ASD models have different variations. Targeting the ApoA-I-SphK pathway will shed new light on therapeutic interventions.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results have shown significant abnormalities of P-ERK and CDK5 in the brains of BTBR mice, which could be rescued by SKI-II intervention. In contrast to our study, other studies have demonstrated that ERK1/2 and CDK5 are both activated in the hippocampus of VPA rats [ 51 ], possibly because different ASD models have different variations. Targeting the ApoA-I-SphK pathway will shed new light on therapeutic interventions.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, 5-HT2A receptor protein immunoreactivity was detected by immunohistochemistry (IHC), using a previously described procedure [ 31 ]. Briefly, endogenous peroxidase was blocked by incubation with 3% H 2 O 2 for 15 min, and sections were incubated overnight at 4 °C in a humidity chamber with primary antibody (1:500 polyclonal anti5-HT2A, catalogue no.…”
Section: Methodsmentioning
confidence: 99%
“…While levels of endogenous or total tau differ across examinations of patients with epilepsy, increased levels of p-tau in the brain are found across many seizure disorders ( Thom et al, 2011 ). These include patients with TLE, Dravet syndrome, Nodding syndrome ( Thom et al, 2011 ; Pollanen et al, 2018 ; Hotterbeekx et al, 2019 ), Niemann-Pick type C disease (NPC) ( Auer et al, 1995 ; Love et al, 1995 ; Suzuki et al, 1995 ; Malnar et al, 2014 ), focal cortical dysplasia IIB (FCDIIb) ( Sen et al, 2007 ; Iyer et al, 2014 ), and tuberous sclerosis complex (TSC) ( Sarnat and Flores-Sarnat, 2015 ; Liu et al, 2020 ), as well as animal models of post-traumatic epilepsy (PTE) ( Cho et al, 2020 ; Alyenbaawi et al, 2021 ), Lafora disease ( Epm2a –/– ) ( Ganesh et al, 2002 ; Puri et al, 2009 ; Machado-Salas et al, 2012 ), and ASD ( Gassowska-Dobrowolska et al, 2021 ). It should be noted that tau aggregation in the brain is associated with older age and is generally uncommon in healthy young adults ( Braak et al, 2011 ; Crary et al, 2014 ).…”
Section: Presence Of P-tau Pathology In Seizure Disorders and Links T...mentioning
confidence: 99%